Surgical Management of Oral Squamous Cell Carcinoma in Dhaka Dental College Hospital; 31 patients (Update Dental College Journal, 2018)
Cancer is a major cause of death throughout the world. Oral cancer is one of the six most frequently occurring cancer.1 In Bangladesh, the number of new cancer cases of whole body per year is about 200000 of which oral cancer is about 20%.2 In our neighboring country India, accounts for thirty-five percent of all newly diagnosed cancers in men. The etiology of oral cancer is well established in most instances with consumption of tobacco in any form and alcohol being the most common etiologic agents. Recently, however, exposure to the human papilloma virus has been implicated in young patients with oral carcinoma. The exact mechanism of carcinogenesis in this setting remains to be elucidated .3 Surgery is the most well established mode of initial definitive treatment for a majority of oral cancers. The factors that affect the choice of treatment are related to the tumor and the patient. Primary site, location, proximity to bone and depth of infiltration are factors, which influence particular surgical approach. Advanced reconstructive techniques that allow free transfer of soft tissue and bone improve the functional and aesthetic outcomes following major ablative surgery .Over the course of the past thirty years there has been improvement in the overall survival of patients with oral carcinoma largely due to the improved understanding of the biology of local progression, early identification and treatment of metastatic lymph nodes in the neck and employment of adjuvant post-operative radiotherapy or chemotherapy. Either the role of surgery in oral cancer has evolved with integration of multidisciplinary treatment approaches employing chemotherapy and radiotherapy sequentially or concurrently .Surgical expertise is required for rehabilitation of functional and aesthetic defects created by initial treatment of cancer. Thus, surgery and services of a surgeon remain central to the management of oral cancer.4 A cross sectional study of 31patients undergoing surgery for the treatment of oral squamous cell carcinoma was carried out at Department of Oral & Maxillofacial Surgery ,Dhaka Dental college & hospital from May 2016 to July2017. Here 31 patients, of them male 13 and female 18 having 31 to 80years age ranges of oral squamous cell carcinoma who underwent surgery and reconstruction were included in this study. All patients were referred to oncologist after surgery. Aim of this study was to assess the status of disease, to provide the patient surgical treatment as a first line therapy, to find out any post-operative complications.Update Dent. Coll. j: 2018; 8 (2): 10-13